Isolation and Identification of Some Bacteria Associated with Biogas Production from Food Waste and Rumen Content - Oladeji, Amoo Afeez; Adeniyi, Adeleye Olarewaju; Adamu, Haruna; Kemi, Amoo Florence; Sabo, Ahmed (CV. Literasi Indonesia, 2024)
The goal of this study was to investigate the bacterial community associated with biogas production from food waste and rumen content. Anaerobic mono-digestion and co-digestion were performed using mixture design within Design Expert, resulting in 100 experimental runs. Parameters such as food waste and rumen content, water content, temperature, pH, number of digester agitation per day and retention time were varied during the anaerobic digestion processes. Classical microbiological techniques were used to isolate and identify strict anaerobic and facultative anaerobic bacteria from the food waste and rumen content before and after anaerobic digestion. Sixteen bacterial species belonging to 12 different generae were isolated and identified from the food waste, rumen content and composite digestates obtained from the 100 bio-digesters. These generae included Acetobacterium, Bacteroides, Clostridium, Enterobacter, Escherichia, Lactobacillus, Pseudomonas, Ruminococcus, Staphylococcus, Streptococcus, Syntrophomonas and Syntrophobacter. With the exception of Escherichia coli and Pseudomonas sp., all other bacterial species identified in the substrates were also found in samples of the composite digestates, suggesting that they may have played important roles in the anaerobic digestion process inside the 100 bio-digesters. Overall, this study provides valuable insights into the microbial community structure and function during biogas production from food waste and rumen content. The results could contribute to the development of more efficient and sustainable biogas production processes.